Generation Gap? The Branching Influence of Historical Myths - Noh, Sung-Chul; Lyle, Matthew C. B.; Do, Boram (Organization Science, 2025)
Despite recent theorizing on the power of rhetorical histories, scholars have yet to consider the dynamics of organizational generations (i.e., collectives defined by temporally proximal organizational entry and shared experiences and memories of organizational events) involved in their creation and long-term effects. Based on a comparative case study of two union organizations that participated in failed initiatives, we produce a parallel process model of cross-generational historical branching explaining the divergent and long-term influences of using history strategically across generational lines. Our model unpacks how theoretically distinct forms of what has been deemed “historical myth” offered by senior generations, while harboring similar utility in building cross-generational support, underlie divergent outcomes regarding how members across generations respond to subsequent failure and, in turn, historically position the initiative. We further suggest these processes have a lingering impact on an organization’s willingness to engage in a subsequent initiative. Our theory sheds light on the ways in which historical myths shared across generational divides, in tandem with the cross-generational mnemonic communities they create, engender divergent, long-term, and potentially unexpected consequences. Funding: This work was supported by Ministry of Education of the Republic of Korea and National Research Foundation of Korea [Grant NRF-2020S1A5A8042404], the Japan Society for the Promotion of Science [KAKENHI Grant JP16K17159], and the Yonsei Signature Research Cluster Program [Grant 2024-22-0167].